Analisis Framing Pemberitaan “Gabung Board of Peace, Indonesia Dukung Kemerdekaan Palestina” pada Website Republika - Najwan Akbar (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
This research examines how Republika.co.id frames the news article "Gabung Board of Peace, Indonesia Dukung Kemerdekaan Palestina," published on 2 February 2026, which reports Indonesia's accession to the United States-initiated Board of Peace as an act of solidarity with Palestinian independence. Using a qualitative case study within a constructivist paradigm, this research applies Robert N. Entman's framing model; define problems, diagnose causes, make moral judgement, and treatment recommendation, supported by an in-depth interview with a communication expert as a method triangulation source. The expert informant agreed to be interviewed on the condition that their identity would remain confidential; therefore, they are referred to in this study as "Communication Expert." The findings show that Republika frames Indonesia's accession not as a contradiction of its Palestine solidarity but as a strategic and legitimate diplomatic step, diagnoses "political opponents" as the cause of the public's misperception, morally justifies the policy through constitutional and humanitarian values, and recommends public trust in the government's diplomatic direction. The article relies on a single source affiliated with the presidential support network, without a counterbalancing perspective, indicating one-sided framing that legitimizes government policy rather than critically scrutinizing it. These findings affirm that Islamic-oriented online media can function as an instrument of political legitimation under an editorial banner of humanitarian solidarity.